Analysis Of Business Feasibility Study On Lion Parcel Kabanjahe - Ginting, Elrisa Marsanda Br; Pasaribu, Anju Christina; Simanjuntak, Lola Vitaloka; Lubis, Putri Kemala Dewi; Saragih, Lenti Susanna (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study aims to conduct a business feasibility study analysis on Lion Parcel in Kabanjahe, Karo Regency. Lion Parcel, as a delivery service, has advantages in delivery speed, affordable prices, and wide area coverage. Lion Parcel has built a trusted capital and operational network with the support of aircraft fleets and high flight frequencies from Lion Air Group as transportation capital to almost all airports in Indonesia. The research method used in this study is qualitative method and elaborated with descriptive analysis to evaluate non-financial aspects of business feasibility studies, such as legal/legality, market and marketing, technical and technological, management and human resources, economic and social, and AMDAL aspects. The information data used in this study is primary data through interviews and secondary company data through the Lion Parcel website. The results of this study show that Lion Parcel Kabanjahe's business is feasible in all non-financial aspects of business feasibility studies so that it can continue its operations and needs to be developed.